(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article analyzes the importance of artificial intelligence (AI) technologies in the strategic management of business systems from both theoretical and practical perspectives. It identifies the limitations of traditional management approaches in the context of the digital economy and substantiates their replacement with data-driven, predictive, and adaptive management models. The role of artificial intelligence in enhancing decision-making processes, reducing risks, optimizing resources, and creating economic value is revealed. In addition, the experience of implementing AI in the telecommunications sector, as well as existing challenges and future prospects, are examined.